Heavy Metal Contamination of Ready-to-use Herbal Remedies in South Eastern Nigeria - Nwoko, Chris O.; Mgbeahuruike, Leo (Pakistan Journal of Nutrition, 2011)
The Zn, Cd and Pb content of selected ready-to-use herbal remedies in Southeast Nigeria were determined by Atomic Absorption spectrophotometer (Model 2380 Perkine Elmer Inc., Norwalk, CT, USA) after acid digestion with 5:1:1 HNO3: HClO4: H2SO4. The concentration levels of Pb, Cd were generally high and above the safe limits set by WHO/FAO. Only Tunya B.fil, Virgy virgy worm expeller and Sekin powder had Zn concentrations above international safe limits representing 20% of the tested herbal remedies. The consumers of these herbal products are inadvertently exposed to heavy metal poisoning. It is important that regulators should intensify efforts to minimize human exposure risk.